Patriotic Mobilization of Orthodox Dioceses of the North-West Territory of Russia during the First World War (August 1914 - Early 1917) - Alexander Yu. Bendin (RUDN Journal of Russian History)
The author examines the issues of the creation and functioning of the mobilization mechanism of institutions and resources of the Orthodox dioceses of the North-West Territory of Russia to provide assistance to the Imperial Russian Army, and to meet the needs of the rear and refugees in the period from the beginning of the war to the fall of the monarchy. The article analyzes the peculiarities of the position of the Russian Orthodox Church in the dioceses of specifically the North-West Territory of Imperial Russia. These peculiarities were due to the tense relations of the Western Russian Orthodox people with Polish Catholicism, which manifested itself in religious and ethnic conflicts and contradictions within the area. The article examines the process of creation of diocesan mechanisms of assistance to the army and the rear, which were based on above on the hierarchically organized system of church authority and discipline, and from below on the patriotic initiative of the Western Russian clergy, monastics, and laity in church institutions and Orthodox brotherhoods. The article analyzes the changes that occurred in the religious and moral state of the Western Russian flock under the influence of the proximity of the Western Front, along social changes in the rear. The author comes to the conclusion that during the war years as a result of patriotic mobilization in the Western Russian dioceses of the Russian Orthodox Church, a kind of military "alliance" was formed between of the Church and the state which was based on common ideological-religious and national-patriotic values of protecting the tsar and the Fatherland.